Selayang Pandang Perlindungan dan Pemberdayaan Pekerja Migran Indonesia - Erisanna, Amelia; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal PKM Manajemen Bisnis, 2025)
Efforts to protect and empower Indonesian Migrant Workers have been carried out through various forms, such as One-Stop Integrated Services and Socio-Economic Empowerment. These efforts prioritize a centralized administration system and community development to overcome various problems faced by Migrant Workers, Former Migrant Workers and their Families. This study uses the literature study method with a content analysis approach. It concludes that efforts to protect and empower have been carried out in various places in Indonesia, and various forms have been implemented. Starting from the administrative side, information socialization, family strengthening, increasing the capacity of PMI abroad and consolidating former PMI. However, these efforts still seem to stand alone. They are not integrated between protection and empowerment, which should be a whole unit in the service of Indonesian Migrant Workers, including the lack of involvement of the private sector and NGOs in efforts to protect and empower.